Synthesis and characterization of hydroxyapatite-based nanocomposite coating with alginate biopolymer and MgO nanoparticles for enhanced antibacterial Properties - Mohammad Moslem Imani; Parya Fatahi; Amin Golshah; Mohammad Salmani Mobarakeh; Mohsen Safaei (Open Ceramics)
The objective of this study is to identify the ideal conditions for fabricating hydroxyapatite/alginate/MgO nanocomposite with potent antibacterial. The Taguchi approach was used to investigate the production of nanocomposites with the outstanding antibacterial properties. Three factors were studied at three levels, resulting in nine unique experiments. Characteristics such as surface appearance, chemical composition, elemental dispersion, thermal analysis and crystal structure were all evaluated. The findings showed that MgO nanoparticles and alginate biopolymer were evenly distributed throughout the hydroxyapatite matrix. The nanocomposite produced under experimental conditions 3 (0.03 M hydroxyapatite, 0.04 M alginate, and 0.08 M MgO) showed the strongest impact in inhibiting the growth of Streptococcus mutans at 1.84 Log10 CFU/ml. This study illustrated that the fabricated nanocomposite had a stable performance under ideal conditions and the use of appropriate levels of components enhance the antibacterial activity of the fabricated nanocomposite.